Faecal sludge emptying in Sub-Saharan Africa, South and Southeast Asia: A systematic review of emptying technology choices, challenges, and improvement initiatives - Muoghalu, Chimdi; Semiyaga, Swaib; Manga, Musa (Frontiers in Environmental Science, 2023)
The emptying and transport of faecal sludge (FS) is a fundamental aspect of the sanitation service chain and is mostly carried out by private operators who usually face a lot of challenges. Our review assessed how influencing factors and challenges FS emptiers face are linked and in turn how they act as barriers to improvement initiatives. We conducted a systematic review of peer-reviewed journals on FS emptying in sub-Saharan Africa, South and Southeast Asia published between January 2002 and December 2021. Amongst the 37 journals reviewed, accessibility was mostly documented (n=18) as a factor which affected choice of emptying method, followed by cost (n=14), quality of service (n=13) and then sludge thickness (n=8). We grouped the types of challenges identified from the publications into five categories of financial, technical and institutional (n=14, each), followed by health (n=12) and then social challenges (n=8). Discussions on initiatives (n =13) used to improve the emptying business were limited to Cost/affordability of sanitation services and access to finance by FS emptiers, which were noted to be the major barriers to effective implementation of these strategies. This review identified the need for sensitizing the public on FS emptying, financial modelling of manual emptying business and a need to study the relationship between perceptions and emptying behavior of users.